Actors have feelings too: An examination of justice climate effects on the psychological well‐being of organizational authority figures. Issue 4 (28th March 2016) - Bernerth, Jeremy B.; Whitman, Daniel S.; Walker, H. Jack; Mitchell, David T.; Taylor, Shannon G.
Abstract : Although a substantial amount of research explores how work units collectively benefit from authority figures who adhere to the rules of justice (i.e., justice climate), virtually no research explores how authority figures themselves benefit from creating a climate of fairness. We draw from relational theories of human behaviour and psychological well‐being to develop a theoretical model of the relationship between justice climate and authority figures' well‐being. Using data from a sample of 1297 employees and 162 authority figures within 162 work units, we find that procedural justice (PJ) and interactional justice (IJ) climate relate to authority figures' occupational satisfaction and emotional exhaustion; IJ climate also relates to positive affect. In addition, in line with an agent‐related justice perspective, IJ climate has a stronger overall impact than PJ climate on authority figures' well‐being. Practitioner points: Finding individuals who want to be organizational authority figures is difficult if there are perceived psychological costs associated with being an authority figure. The reported research suggests organizations may want to highlight the positive relationship between adherence to rules of justice and the psychological well‐being of authority figures as a potential benefit of assuming authority positions. Whereas traditional approaches to job design suggest the redesign of significant portions of the job (which is not always practical), our results suggest large‐scale changes may not be the only method for enhancing the positive feelings authority figures have about their job. Organizations could instead emphasize the positive impact that authority figures have on the work group as a whole. Given that working closely with the beneficiaries of one's efforts is intrinsically gratifying, such an emphasis might be enough to help create a more healthy and enjoyable environment for organizational authority figures. Managers should pay particular attention to the interpersonal interactions they have with their employees. Our results suggest it is the interpersonal component of justice climate, as compared to the more process‐ or policy‐oriented components, that is the most beneficial to organizational authority figures.